2015
DOI: 10.3390/rs70505300
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Conventional and Advanced DInSAR to Monitor Very Fast Mining Subsidence with TerraSAR-X Data: Bytom City (Poland)

Abstract: In this work,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 107 publications
(84 citation statements)
references
References 31 publications
1
83
0
Order By: Relevance
“…SqueeSAR incorporates PSInSAR and no information is lost. Przylucka et al 35 have shown the capabilities of SqueeSAR for detecting and monitoring mining subsidence in urban areas of the upper Silesian coal basin of Poland. The complexity of open-pit iron mining in Carajás Mineral Province, Brazil, makes DInSAR a challenging application.…”
Section: Analyses On Applications Of Dinsar In Surface Subsidencementioning
confidence: 99%
See 4 more Smart Citations
“…SqueeSAR incorporates PSInSAR and no information is lost. Przylucka et al 35 have shown the capabilities of SqueeSAR for detecting and monitoring mining subsidence in urban areas of the upper Silesian coal basin of Poland. The complexity of open-pit iron mining in Carajás Mineral Province, Brazil, makes DInSAR a challenging application.…”
Section: Analyses On Applications Of Dinsar In Surface Subsidencementioning
confidence: 99%
“…They established the relevance of the PSInSAR technique in studying the deformation before the major subsidence, when no levelling data were recorded. Przylucka et al 35 demonstrated that using high-resolution TerraSAR-X data in both conventional and advanced DInSAR approaches was effective for detecting and monitoring fast-evolving mining subsidence in urban areas in the upper Silesian coal basin of Poland. The main design parameters that influence the feasibility and accuracy of PSInSAR are the number of acquisitions (images; N), the temporal baseline (B T ) and spatial/perpendicular baseline (B  ).…”
Section: Analyses On Applications Of Dinsar In Surface Subsidencementioning
confidence: 99%
See 3 more Smart Citations